2014
DOI: 10.1615/jpormedia.v17.i11.10
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Effects in Light/Medium Oil Recovery by Air Injection: Vaporization vs. Combustion

Abstract: Combustion can be used to enhance recovery of heavy, medium, or light oil in highly heterogeneous reservoirs. Such broad range of applicability is attained because not only do the high temperatures increase the mobility of viscous oils but also the high thermal diffusion spreads the heat evenly and reduces heterogeneity effects. For the latter reason, combustion is also used for the recovery of light oils. The reaction mechanisms are different for light oils, where vaporization is dominant, whereas for medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In a previous theoretical study based on two-component oil model, we found that the ratio between vaporization and reaction determines the effectiveness of the air injection process [31]. If a large amount of heavy components is present in oil, the vaporization is weak and most oil is left behind for combustion.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a previous theoretical study based on two-component oil model, we found that the ratio between vaporization and reaction determines the effectiveness of the air injection process [31]. If a large amount of heavy components is present in oil, the vaporization is weak and most oil is left behind for combustion.…”
Section: Introductionmentioning
confidence: 96%
“…One of the purposes of our research is to investigate whether we can find experimental evidence for the medium temperature combustion mechanism described theoretically in [40,31]. We perform and interpret experiments involving air injection in sandstone rock filled with n-hexadecane (modeling light oil) at medium pressures and conditions that are typical away from the injection well.…”
Section: Introductionmentioning
confidence: 99%
“…Air injection techniques can offer unique benefits and technical opportunities for enhanced oil recovery (EOR) in many candidate reservoirs for both conventional and unconventional oil sources, such as high pressure air injection (HPAI) for water-flooded light oil reservoirs and low permeability reservoirs where water injection is difficult (conventional oil sources), in situ combustion (ISC) for heavy oil reservoirs, bitumen sands and shale oil (unconventional oil sources). After air is injected into reservoirs, various oxidation reactions take place between crude oils and oxygen contained in the injected air, which generates heat to reduce oil viscosity (especially for ISC in heavy oil reservoirs) and flue gas to improve swept volume and increase reservoir pressure . It is acknowledged that oxidation reactions between crude oil and injected air dictate the overall success of the air injection processes .…”
Section: Introductionmentioning
confidence: 99%
“…During in situ combustion processes, it is expected that hydrocarbons/heavy oil/ bitumen and the oxygen-enriched injected air react and interact, resulting in inevitable chemical changes due to the chemical reactions involved. As shown in Figure 3, the reaction zones across the reservoir can be categorized into three different temperature ranges: (1) low-temperature reactions (reservoir temperature up to 300 • C; LTO), (2) medium-temperature reactions (300-350 • C; MTO), and (3) high-temperature reactions (350-525 • C; HTO) [24,[47][48][49][50][51]. The three ISC kinetic regimes are briefly summarized in Table 3, and further details are provided in the following subsections.…”
mentioning
confidence: 99%